Geraldine - Lilly, Elizabeth (Elizabeth Marie) (Roaring Brook Press, 2018)
Struggling to fit in as the only giraffe in a school of children, reluctant newcomer Geraldine meets fellow outcast Cassie and learns how to stand out by being herself, playing by her own rules, and staying true to her new friend.